Design and Build an ENT Disease Diagnosis Expert System with Bayesian Probability Method - Khairina Eka Setyaputri; Hidayatur Rakhmawati (IJISTECH (International Journal of Information System and Technology), 2021)
Sinusitis is one of the most common causes of health problems in the world and the cases are most often found in daily practice. The incidence of sinusitis is a fairly severe disease, namely 1.3 and 3.5 per 100 cases of adults per year to see a doctor. Patients with a disease need accurate information that is easily accessible to find out the disease they are experiencing based on the symptoms they feel. One of the reliable information sourced from experts or people who are experts in their fields and can be easily accessed is the existence of an expert system. In this case, the expert system needed is an ENT (Ear, Nose and Throat) disease diagnosis expert system. The expert system for diagnosing ENT diseases, designed in this study uses the Bayesian Probability method. The research on the design of an expert system for diagnosing ENT diseases that have been carried out can be used as a decision making for ENT patients using the Bayesian Probability method.